Pengaruh Pengungkapan Emisi Karbon, Ukuran Perusahaan, dan Profitabilitas Terhadap Nilai Perusahaan yang Terdaftar di BEI (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to determine the effect of carbon emission disclosure, company size, and profitability on the value of mining companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach with an expalanatory research approach. The research sample was obtained using a purposive sampling method with 17 compaies over three years, 2021-2023, resulting in a total of 51 observations. The dependent variables in this study is company value, measured using Tobin’s Q, while the independent variables include carbon emissions disclosure, measured using the Carbon Disclosure Project (CDP) checklist method, company size, measured using the natural logarithm (Ln) of total assets, and profitability, measured by Return On Assets (ROA). Data analysis was performed using muitiple linear regression with the help of SPSS. The results of this study indicate that carbon emissions disclosure and profitability have a positive and significant effect on firm value. Homever, firm size does not signifcantly influence firm value. Keywords: Carbon Emissions Disclosure, Firm Size, Profitability, Firm Value.